Does energy transition matter to sustainable development in ASEAN? - Mu'min, M. Silahul; Yaqin, Misbahol; Anam, Muhammad Syariful (Center of Biomass & Renewable Energy (CBIORE), 2024)
The energy transition towards renewable sources represents a pivotal factor in pursuing sustainable development. This study reviews the impact of renewable energy on three aspects of sustainable development, namely economic, social, and environmental aspects in ASEAN. To quantify these aspects, GDP per capita proxies for the economic dimension, unemployment rates for the social dimension, and CO2 emissions for the environmental dimension. The data used is panel data of 10 ASEAN countries from 1996-2020. Pooled Mean Group (PMG) estimation technique is applied to identify the relationship between renewable energy and the dimensions of sustainable development. The study results reveal that renewable energy has a significant influence on sustainable development in the long run. Specifically, renewable energy is able to stimulate GDP per capita levels, thus potentially serving as a determinant of sustainable economic growth in ASEAN. Furthermore, the findings of this study suggest that renewable energy has the capacity to reduce CO2 emissions in the long run. Efforts to increase the share of renewable energy usage are needed to mitigate the risk of environmental degradation. However, it is noteworthy that our study underscores the adverse impact of the energy transition on the social dimension, as it can potentially drive-up unemployment rates in the long run. This impact can be attributed to labor market relocations and structural changes. Novice workers in the renewable energy sector may face the risk of displacement. Consequently, this study has implications that underscore the need for inclusive approaches to elevate the usage of renewable energy. Furthermore, a well-structured policy framework is needed to encourage more investments and prepare the competent workforce in the renewable energy sector.